Meclofenamic Acid Restores Gefinitib Sensitivity by Downregulating Breast Cancer Resistance Protein and Multidrug Resistance Protein 7 via FTO/m6A-Demethylation/c-Myc in Non-Small Cell Lung Cancer - Chen, Hui; Jia, Bin; Zhang, Qiang; Zhang, Yu (Frontiers in Oncology, 2022)
Background and Objective Gefitinib (GE) is a first-line epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) for patients with advanced non-small cell lung cancer (NSCLC) carrying EGFR activating mutations. However, drug resistance limits the clinical efficacy of gefitinib and ultimately leads to extremely poor clinical benefit. Meclofenamic acid (MA) is a non-steroidal anti-inflammatory drug (NSAID) that relieves moderate and severe pain. In the present study, we aim to determine the MA sensibilization of GE in NSCLC. Methods MTT assay was conducted to determine the synergistic effect of MA with GE in GE-sensitive and -resistant cell lines based on the Chou–Talalay method. The Annexin V-PI flow cytometry analysis was conducted to evaluate apoptosis. Western blot assay was used to detect alterations of EGFR downstream molecules. Tritium-labeled GE accumulation analysis was used to determine the efflux activity of GE. Dot blot assays were conducted to determine m6A levels after the MA and GE co-administration. Western blot evaluated the expression of FTO, c-Myc, MRP7, BCRP, and apoptotic proteins. Results MA showed a significant synergistic effect with GE in GE-resistant NSCLC cells; co-administration of MA with GE induced caspase-related apoptosis in resistant NSCLC cells. Moreover, EGFR downstream molecules, including Akt and MAPKs pathways, were significantly inhibited by the MA-GE combination. Short-term incubation of MA did not alter the efflux of GE; however, after incubation for 24 h, the accumulation of tritium-labeled GE significantly increased. A mechanism study showed that co-administration of MA and GE significantly downregulated BCRP and MRP7 expression in GE-resistant cells; increased N6-methylation was also observed after co-administration. The FTO/c-Myc was determined as target pathways on MA and GE co-administration mechanisms. Conclusion Our findings provide novel therapeutic approaches for GE-resistant NSCLC by combination use with MA through FTO-mediated N6-demethylation.